2017
DOI: 10.1080/10376178.2017.1290537
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve self-management in heart failure patients

Abstract: Improved self-management will increase compliance, promote patient quality-of-life, advance clinical outcomes, reduce hospital re-admission and will decrease hospitalization costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 93 publications
2
44
0
Order By: Relevance
“… 2 Effective two-way communication between people with HF and health-care professionals (HCPs) is key to improving patients’ knowledge and understanding of their heart condition and associated with improvements in both adherence to HF-management plans 3 , 4 and patient outcomes. 5 , 6 Communication between patients and HCPs is also needed to aid decisions on pharmacological treatment. It is important that patients are involved in these decisions so that they understand how to take their medication (dose, time of day) and the benefits of treatment, and are able to recognize possible side effects of pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Effective two-way communication between people with HF and health-care professionals (HCPs) is key to improving patients’ knowledge and understanding of their heart condition and associated with improvements in both adherence to HF-management plans 3 , 4 and patient outcomes. 5 , 6 Communication between patients and HCPs is also needed to aid decisions on pharmacological treatment. It is important that patients are involved in these decisions so that they understand how to take their medication (dose, time of day) and the benefits of treatment, and are able to recognize possible side effects of pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Silavanich et al [48] found a positive relationship between medication adherence and QoL among 180 HF patients. Adherence to diet (low sodium and low fat), to medication and to fluid restrictions positively affects QoL, and prevents hospitalizations and death, whereas non-adherence is associated with symptom deterioration [49,50]. Having as the ultimate goal to improve QoL, it is crucial to enhance adherence in several ways such as psychosocial support, education, counseling, and scheduled telephone contacts, to evaluate self-efficacy behaviors [51].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this information, heart failure patients seem to have poor basic knowledge about their condition, and adherence to self-care behaviors is low (Jaarsma et al, 2013; Spaling et al, 2015; Stut et al, 2015). Suboptimal self-care behaviors are correlated with mortality and quality of life (Seto et al, 2011; Stut et al, 2015; Toback & Clark, 2017). However, improved self-care behaviors can reduce the risk for hospital (re)admissions (Chamberlain, 2017; Lee, Moser, Lennie, & Riegel, 2011; Toback & Clark, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal self-care behaviors are correlated with mortality and quality of life (Seto et al, 2011; Stut et al, 2015; Toback & Clark, 2017). However, improved self-care behaviors can reduce the risk for hospital (re)admissions (Chamberlain, 2017; Lee, Moser, Lennie, & Riegel, 2011; Toback & Clark, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation